Corporate Crime Liability as the Subject of Corruption Act based on the Return of State Financial Losses: Array - Sibarani, Mery Rohana Lisbeth (Acta Universitatis Danubius. Juridica, 2021)
The development of legal subjects in corruption has been changing. If formerly the punishment is only burdened to the subject of a person, now the legal entities, including corporation, are also burdened with the penalty. This study aimed to understand and analyze the liability of a corporate in its criminal act based on the return of state financial losses. The methodology used in this study was juridical normative (legal research) using statue and conceptual approach. The results showed that, conceptually, the return of state financial losses can still be done even though there are still some obstacles in terms of procedural or technical structure. However, the fact is criminal acts in the form of state money are not only received or enjoyed by the defendant, but also by the third party (non-defendant). Therefore, the penalty in the form of replacement money can be applied for corporate. Replacement money is one of the additional criminal penalty in corruption case that must be paid by the convict to the state with the amount as much as the property obtained from the corruption. In summary, an accurate and effective legal method or instrument is needed to return the state’s financial losses.